ANALISIS PENERAPAN AKUNTANSI BERDASARKAN ISAK 35 PADA KANTOR LEMBAGA BANTUAN HUKUM MAHARDIKA JAMBI - Hermawati, Arum; Fathurrahman; Khairiyani (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2024)
This study aims to apply accounting based on ISAK 35 at the office of the Mahardika Legal Aid Institute The concept of ISAK 35 allows non-profit oriented entities to adjust the description used by financial statements and the financial statements themselves include statements of financial position, comprehensive income statements, statements of changes in net assets, statements of cash flows, and notes to financial statements At the Mahardika Legal Aid Institute has not implemented or made reports to these financial statements. The purpose of this study is to find out how the presentation of financial statements at the Legal Aid Institute. The types of data used are primary data and secondary data. Data collection techniques are carried out using interview and documentation techniques. The data analysis method used is qualitative descriptive, which is a method that describes, describes, compares data and circumstances and explains a situation in such a way that a conclusion can be drawn. The research was conducted at the Mahardika Engineering Legal Aid Institute research. Based on the results of the analysis, the financial statements of the Mahardika Legal Aid Institute are not in accordance with ISAK 35 because the presentation of the financial statements of the Mahardika Legal Aid Institute still uses simple recording. The financial statements of the Mahardika Legal Aid Institute have not made a statement of financial position, comprehensive income statement, statement of changes in net assets, statement of cash flows, and notes to financial statements.